SPECIFIC PRECAUTIONS FOR AVOIDING MICROORGANISM TRANSMISSION: DEVELOPMENT AND VALIDATION OF AN EDUCATIONAL GUIDE - Luize Fábrega Juskevicius; Maria Clara Padoveze (Universidade Federal do Paraná, 2016)
This study aimed to develop and validate the content of the educational guide for individuals under specific precautions for avoiding microorganism transmission. It is a methodological study performed in three phases, in two hospitals (public and private) in the city of São Paulo, from May to July 2015, using the theoretical framework of Vulnerability. In the first phase, a questionnaire was applied for capturing the adult individuals' perceptions regarding specific precautions. In the second phase, the educational guide was elaborated. In the third phase, the guide was submitted to specialists in specific precautions and vulnerability for content validation. Interviews were held with 39 individuals, an average of seven days after the institution of the specific precautions, 32 (82%) of whom were under contact precautions. The guide was developed to provide better knowledge of aspects usually neglected by professionals, and to encourage person-centred care. All items had a content validity index of above 75%. The guide presents potential to support professionals in the development of educational actions for adult patients subject to specific precautions.